(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
This study focuses on using corn biomass-derived activated carbon to remove benzene and toluene (BT) from water, pollutants that are commonly found due to human activities and accidents like oil spills. The study explores cost-effective adsorption techniques and tests the activated carbon in a continuous fluidized bed column. Toluene is better adsorbed due to its lower solubility. Optimal conditions were identified: 10 cm bed height, 15 mL/min flow rate, and 30°C temperature. According to the breakthrough curve, the maximum adsorption capacity was 0.1447 and 0.15643 (mg/g) with total removal efficacies of 46.72% and 44.894% for benzene and toluene, respectively. The study shows the potential of this method for efficient BT removal, offering insights for water purification and environmental cleanup.